The Mathematical Study of an Edge Crack in Two Different Specified Models under Time-Harmonic Wave Disturbance - Trivedi N.; Das S.; Craciun E.-M. (My University, 2025)
This paper devotes to determining a stress intensity factor (SIF) at the tip of an edge crack in two models considered. Problem-1 is an orthotropic strip of a finite thickness bonded by an orthotropic half-plane, and problem-2 is an orthotropic vertical semi-infinite strip of the same thickness. Edge cracks have been invaded perpendicularly by time-harmonic elastic waves. The models considered were taken to the transformed plane by using the Fourier transform technique, where the Schmidt method is used to find the unknown coefficients. The analytical expression of the SIF is derived for both the problems. The variations of normalized SIF for the different crack lengths and thickness of the strips for the problems considered were calculated numerically, and their behaviour was depicted graphically for different particular cases. © 2022, Springer Science+Business Media, LLC, part of Springer Nature.